Results of proteinuria measurement using semiquantitative dipstick in children with fever or nephrotic syndrome - Chatidjah Alaydrus; Yati Soenarto; M. P. Damanik (Indonesian Pediatric Society Publishing House, 2008)
Background Proteinuria is a major determinant of the progression of renal disease. Quantitative measurement of proteinuria within a 24-hour period of urine collection was the accepted method of evaluation, but is tedious and prone to error in the absence of a reliable collection. We evaluated the diagnostic value of AUTION Sticks 10 TA to diagnose proteinuria in children with fever and nephrotic syndrome. Methods This study was conducted at the pediatric ward of Sardjito Hospital. Proteinuria levels were measured using semiquantitative dipstick methods with AUTION Sticks 10 TA using a 24-hour urine sample collected at the first examination until the following day. Proteinuria level was also measured by Esbach method as gold standard. Results A total of 120 children aged 16 years old were recruited. In the fever group, AUTION Sticks 10 TA couldn't be used for the diagnostic test. AUTION Sticks 10 TA +2 to diagnose intermediate proteinuria produced a sensitivity of 60%, a specificity of 89%, a positive predictive value of 43% , a negative predictive value of 94%, a positive likelihood ratio of 5.4, a negative likelihood ratio of 0.45. To diagnose nephrotic proteinuria, AUTION Sticks 10 TA +3/+4 produced a sensitivity of 90%, a specificity of 91%, a positive predictive value of 96%, a negative predictive value of 77%, a positive likelihood ratio of 10, a negative likelihood ratio of 0.11. Conclusion AUTION Sticks 10 TA +2 is sufficiently accurate for a diagnostic test of intermediate proteinuria (Esbach value) while +3/+4 is sufficiently accurate for a diagnostic test of nephrotic proteinuria (Esbach value) in children. In the fever group, dipstick result can not explain the Esbach value.